2017
DOI: 10.1155/2017/9152973
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Dye-Sensitized Solar Cells Efficiency Using Mixed-Phase TiO2 Nanoparticles as Photoanode

Abstract: Dye-sensitized solar cell (DSSC) is a potential candidate to replace conventional silicon-based solar cells because of high efficiency, cheap cost, and lower energy consumption in comparison with silicon chip manufacture. In this report, mixed-phase (anatase and rutile nanoparticles) TiO2 photoanode was synthesized to investigate material characteristics, carriers transport, and photovoltaic performance for future DSSC application. Field-emission scanning electron microscope (SEM), X-ray diffraction (XRD), pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 25 publications
2
10
0
Order By: Relevance
“…However, the best photoelectrical parameters were achieved for DSC based on the TiO 2 layer with the anatase/rutile ratio of 84/16% [19]. These results suggest the existence of another positive impact of rutile addition on the PCE that dominates the effect of the specific surface decrease [20]. Similar phenomena described in references [21,22] also confirms this suggestion.…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…However, the best photoelectrical parameters were achieved for DSC based on the TiO 2 layer with the anatase/rutile ratio of 84/16% [19]. These results suggest the existence of another positive impact of rutile addition on the PCE that dominates the effect of the specific surface decrease [20]. Similar phenomena described in references [21,22] also confirms this suggestion.…”
Section: Introductionsupporting
confidence: 81%
“…Previously several studies were performed on the investigation of the dependence of dye-sensitized solar cells (DSCs) performance on the anatase/rutile phase ratio in the nanostructured mesoscopic photoelectrodes [18][19][20]. It was found that the addition of the rutile to anatase in the range of 10-15% significantly improved light harvesting and the overall power conversion efficiency of DSCs [18].…”
Section: Introductionmentioning
confidence: 99%
“…The degree of recombination rates can be used to check the efficiency of electron transfers. High recombination center of pure rutile shows photocatalytic inactive in comparison with anatase 47 …”
Section: Resultsmentioning
confidence: 99%
“…High recombination center of pure rutile shows photocatalytic inactive in comparison with anatase. 47 Thin films of pure TiO 2 and 1% Ag-TiO 2 were successfully prepared using sol-gel technique. These films are irradiated by Ni ions.…”
Section: Band Gap Analysismentioning
confidence: 99%
“…When the exciton binding energy of LAMs is lower than the thermal energy, the planar thin-film structure can be used to construct the high-performance solar cells, such as the crystalline Si [6,7], crystalline GaAs [8,9] and crystalline InP [10,11] solar cells. When the exciton binding energy of the LAMs is higher than the thermal energy, the P:N nanocomposite thin-film structures have to be used to increase the photovoltaic performance, such as the organic bulk-heterojunction solar cells [12,13,14] and dye-sensitized solar cells (DSSCs) [15,16,17]. Although the PCE of organic photovoltaics (OPVs) and DSSCs is significantly lower than that of the planar thin-film inorganic semiconductor-based solar cells, the cost-effective OPVs and DSSCs still received a lot of attentions in the past two decades.…”
Section: Introductionmentioning
confidence: 99%